Anaemia – Is there any solution? - Rao, Bhagya Venkanna (Journal of Pharmacy Practice and Community Medicine)
Anaemia is the condition where the oxygen-carrying capacity of RBC decreased. Prevalence is very high in India and other developing countries. Reasons vary from poorer socio-economic status, lower education among women, indigent access to healthcare facilities and many more.